Land and freshwater snails of Imbak Canyon Conservation Area (ICCA), Sabah, Northern Borneo - Chang, Zi-Yuan; Phung, Chee Chean; Eric Goundilang; Liew, Thor Seng (Universiti Malaysia Sabah, 2019)
This paper presents the first checklist of land and freshwater snails of Imbak Canyon Conservation Area (ICCA) as part of the Imbak Crayon Scientific Expedition 2017. The specimens of land and freshwater snails were collected from six standard sampling plots and several random locations around Batu Timbang Basecamp between 17th and 19th August 2017. A total of 21 species of land snail and one species of freshwater snail are presented in a checklist. Currently, 24 species of land snails and one species of freshwater snail are recorded in ICCA, after including two species that were previously recorded but yet to be published.